Brick The Book : 16 Designers, Architects + Artists Show the Latest in Brick Design for the Facade of the Future : Publication of .EKWC'S Brick Project 2005-2007. - Erven, René; Zwinkels, Noor ('s-Hertogenbosch : European Ceramic Work Centre, 2007)
Bijlenga, Marian ; Binns, David ; Bremner, Alasdair ; Burton, Andrew ; Danielsen, Hilde ; Douglis, Evan ; Florians, Martina ; Jetten, Christine ; Tunick, Susan ; NEXT Architects ; Oostrum, Ben ; Bonneur, Rob ; Pauwels, Marieke ; Posthuma, Rem ; Rojas, José ; Saalfeld, Christine ; Schabert, Jan ; Trenning, Baukje ; Visser, Arnaot ; Kwakkel, Erik-Jan
Brick: The Exhibition, Groot Handelsgebouw, Rotterdam, 25 May - 1 July 2007
boek